Generalized Symmetries of Massless Free Fields on Minkowski Space - Pohjanpelto, J.; Anco, S.C. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
A complete and explicit classification of generalized, or local, symmetries of massless free fields of spin s ≥ 1/2 is carried out. Up to equivalence, these are found to consists of the conformal symmetries and their duals, new chiral symmetries of order 2s, and their higher-order extensions obtained by Lie differentiation with respect to conformal Killing vectors. In particular, the results yield a complete classification of generalized symmetries of the Dirac-Weyl neutrino equation, Maxwell's equations, and the linearized gravity equations.